Crisis and commercialisation of insanity under the aegis of Brazilian conservationism - Jesus, Amanda Silva de; Santos, Sandra Rodrigues dos (Argumentum, 2023)
This study discusses mental health measures that have been consolidated in Brazil, taking into consideration the structural crisis of capital and the deepening of conservatism in Brazil, which have directly affected the equitable development of this policy. The results indicate that actions implemented during the Temer administration and their impact on the preservation of acquired rights had a significant impact on Mental Health Policy. Through qualitative literature review, it aims to understand how the counter-reforms implemented in recent years have influenced the National Policy on Mental Health, Alcohol and Other Drugs, reinforcing the current expressions of the social question, and confirming the resurgence of the asylum model, which has led to a retrogression of the solid achievements of the Psychiatric Reform Movement that had been in place since the 1980s.